PENGARUH DIVIDEN, HUTANG, INVESTASI, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (Studi Kasus Sektor Aneka Industri di Bursa Efek Indonesia 2012-2014) - Lia Indrayanti; Rikha Muftia Khoirunnisa (Jurnal Fokus Manajemen Bisnis, 2016)
This study aims to examine the effect of dividends, debt, investment, and profitability to firm value (case studies of various sectors industry on the Indonesia Stock Exchange 2012-2014). The sample in this study is companies in various industrial sectors. Deep sampling technique. This research uses purposive sampling technique, obtained 7 samples companies in various industrial sectors. Test by using a test statistical analysis of multiple linear regression. Partially, statistical tests are used is the t test and simultaneously with the F test. Based on the results the research can be concluded that partially dividends have no effect to the value of the company in various industrial sectors, debt, investment, and profitability affects the value of the company in various industrial sectors, and simultaneously dividends, debt, investment, and profitability have an effect to the value of the company in various industrial sectors.